PELATIHAN PEMANFAATAN LIMBAH CANGKANG KERANG DAN KEMASAN DETERGEN MENJADI POT BUNGA DAN KOTAK PENSIL SECARA KREATIF SISWA KELAS VI SD NEGERI 05 DESA MUARA GADING MAS KECAMATAN LABUHAN MARINGGAI - Lailatul Hidayah; Amara Amara; Hendra Hafid Parmadi; Yoanda Yoanda; Ilham Saputra Isnel; Muthie Apriyanti; Femi Alya Juwita; Nuki Puspitasari (Universitas Ichsan Sidenreng Rappang, 2024)
Coastal areas are areas that have abundant marine potential. One of the potentials is the large number of marine products that can be used, such as shellfish and fish. With so many natural products being used, such as shellfish, this has resulted in a buildup of shellfish waste. The waste in coastal areas does not only come from shells, but also a lot of it comes from household waste such as plastic waste from detergent packaging. Seeing this, all the IAIN Metro Real Work Lecture (KKN) students carrying out community service in Muara Gading Mas Village were inspired to utilize this waste into more useful products. By working together with SD Negeri 05 Muara Gading Mas Village, community service students carried out training activities on the use of shell waste and detergent packaging to make flower pots and pencil boxes with class VI students. The aim is to provide education to class VI students to help reduce the accumulation of waste by utilizing waste shells and detergent packaging into products that can be used and become economical goods. The methods used include delivering material in the form of presentations, demonstrations, and assistance in making products. This activity was successfully carried out due to the support and enthusiasm of the students in learning and understanding the material presented.